Community Dogma: Transactional Relations of the Suli Indah Village Community Cooperative - Alit Darmawan; Latifah Sukmawati Yuniar; Rahayu Indriasari; Nina Yusnita Yamin; Arif Gunarsa (UNIVED Press, 2026)
The role of religious dogma shapes the belief system that affects the accountability of cooperative financial management. This research aims to find the meaning of cooperative accountability in the prescriptive Hindu dogma. The research locus is in Suli Indah Village, where the majority of the population is Hindu. A qualitative approach with phenomenological methods is used to explore the experience and subjective meaning of society. Data was obtained through in-depth interviews with managers and cooperative members as well as observation of financial practices. The results show that cooperatives are interpreted not only as economic institutions, but as a moral and spiritual space based on Dharma, honesty (Satya), solidarity, and social responsibility. Public trust is formed through collective experience, social closeness, and the perception of ethical and transparent accounting practices. Cooperatives are understood as Dharma Barns, where accountability is exercised as a moral and spiritual obligation, with dogma as the social legitimacy of the sustainability of cultural value-based practices.